Vocational Core Competence in Higher Vocational Education - Sun, Huayun (Journal of Theory and Practice of Humanities Science, 2023)
From the perspective of talent training objectives, material engineering technology major cultivates highly skilled talents with comprehensive production process knowledge and management knowledge of material engineering technology and strong practical ability, who are oriented to the first line needs of production, construction, management and service. Refractory industry at present, the whole foundation is relatively weak, refractory resource utilization level is low, the quality of the refractory grade is not high, excess production capacity, the ordinary products some high quality high technology content of key products can production, but the quality is not stable, service life and refractory consumption compared with foreign advanced level, there is a considerable gap. the fundamental reason is the lack of high-level talents. To better meet the iron and steel, machinery, chemical industry, power and other industries to the needs of the refractory material, must be to the professional production and technical management personnel's quality and ability are put forward new requirement, not only can be competent the job requirements of the current position, and should have the ability of learning new technology, to adapt to the new job, it is particularly important in today's high-tech.